Recuperación de oro en la lixiviación alcalina por agitación utilizando goldmax como agente alternativo al cianuro de sodio. - Merizalde Robles, Jessica Stefania; Vivanco Suarez, Byron Alexander (Machala : Universidad Técnica de Machala, 2020)
In the present study, the recovery process of gold ore was evaluated by applying GoldMax solutions as an alternative to sodium cyanide in agitated leaching of gold at laboratory scale. Through a factorial design, three factors and two levels were evaluated: GoldMax leaching concentration at 200 and 600 ppm; leaching time at 48 and 60 hours; pulp density at 1.2 and 1.3 g / ml. Evaluating each factor with its respective level, it resulted in 11 experimental tests with three replicas at the central point, each test the pH level was measured to keep it at 11 and prevent the reagent from degrading and help sediment the mineral particles. The gold ore used in the experimental part of the investigation was obtained from the processing of the Chilean mill of the “Agapitos” Benefit Plant, located at the El Pache site of the city of Portovelo in the province of Oro. Applying a technique known as quartet 10kg of representative sample was obtained. It was subjected to a drying process for 12h at 105 ° C, then treated by a sieving process allowing us to separate the sample at 150 (µm) of particle size. This mineral is characteristic for being of gold deposits associated with sulphides and free gold, which are the mineralized forms with the greatest commercial boom.
En el presente estudio, se evaluó el proceso de recuperación de mineral aurífero mediante la aplicación de soluciones de GoldMax como alternativa del cianuro de sodio en la lixiviación agitada de oro a escala laboratorio. Mediante un diseño factorial se evaluaron tres factores y dos niveles: concentración del lixiviante GoldMax a 200 y 600 ppm; tiempo de lixiviación a 48 y 60 horas; densidad de pulpa a 1,2 y 1,3 g/ml. Evaluando cada factor con su respectivo nivel, nos dio como resultado 11 pruebas experimentales con tres replicas en el punto central, cada prueba se midió el nivel de pH para mantenerlo en 11 y evitar que el reactivo se degradara y ayudar a sedimentar las partículas del mineral. El mineral aurífero empleado en la parte experimental de la investigación se obtuvo del procesamiento del molino chileno de la Planta de Beneficio “Agapitos”, ubicada en el sitio El Pache de la ciudad de Portovelo en la provincia del Oro. Aplicando una técnica conocida como cuarteo se logró obtener 10kg de muestra representativa. Se lo sometió a un proceso de secado por 12h a 105ºC, luego se trató por un proceso de tamizado permitiéndonos separar la muestra a 150 (µm) de granulometría. Este mineral es característico por ser de yacimientos de oro asociado a sulfuros y oro libre, que son las formas mineralizadas con mayor auge comercial.
Keywords: GOLDMAX; LIXIVIACION; DENSIDAD DE PULPA; METALURGIA